Incomplete Form of Shone Complex in an Adult Congenital Heart Disease Patient - Shih, Beatrice Chia-Hui (Korean J Thorac Cardiovasc Surg, 2019)
Shone complex is a rare congenital disorder that involves 4 obstructive lesions of the left heart, as follows: parachute mitral valve, supravalvular mitral ring, subaortic stenosis, and coarctation of the aorta. Incomplete forms with 2 or 3 of these lesions in adult patients have been rarely reported in the literature, meaning that insufficient general data exist concerning the surgical strategy and clinical follow-up. Herein, we report the case of a 31-year-old woman with a diagnosis of incomplete form of Shone complex with parachute mitral valve and coarctation of the aorta who underwent successful single-stage surgical repair.